2005
DOI: 10.1136/gut.2004.050781
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors predictive of mortality in alcoholic hepatitis and derivation and validation of the Glasgow alcoholic hepatitis score

Abstract: Introduction: Alcoholic hepatitis is associated with a high short term mortality. We aimed to identify those factors associated with mortality and define a simple score which would predict outcome in our population. Methods: We identified 241 patients with alcoholic hepatitis. Clinical and laboratory data were recorded on the day of admission (day 1) and on days 6-9. Stepwise logistic regression was used to identify variables related to outcome at 28 days and 84 days after admission. These variables were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
239
0
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(251 citation statements)
references
References 15 publications
4
239
0
8
Order By: Relevance
“…4). In terms of diagnostic accuracy for prediction of death, the 0.45 Lille score cutoff was more efficient than our previous simple criterion referred to as ECBL 12 (P ϭ 0.001) and the proposed cutoff of 9 for the Glasgow score 17 (P Ͻ 0.01). In terms of number of predicted deaths, the 0.45 cutoff of the Lille model was able to identify 75.6% of the observed deaths, whereas ECBL and the cutoff of 9 for the Glasgow score were able to identify 62.5% and 64.5%, respectively.…”
Section: New Management Based On the Lille Modelmentioning
confidence: 95%
See 2 more Smart Citations
“…4). In terms of diagnostic accuracy for prediction of death, the 0.45 Lille score cutoff was more efficient than our previous simple criterion referred to as ECBL 12 (P ϭ 0.001) and the proposed cutoff of 9 for the Glasgow score 17 (P Ͻ 0.01). In terms of number of predicted deaths, the 0.45 cutoff of the Lille model was able to identify 75.6% of the observed deaths, whereas ECBL and the cutoff of 9 for the Glasgow score were able to identify 62.5% and 64.5%, respectively.…”
Section: New Management Based On the Lille Modelmentioning
confidence: 95%
“…However, we lack evidence supporting the higher efficacy of new models such as MELD and Glasgow scores compared with the DF. [16][17][18] In the particular setting of patients treated by corticosteroids, new specific models could pose a challenge to clinical practitioners by inciting them to consider all available options in targeted patients after a short period of evaluation. 15,19,20 The aims of the current study on a large cohort of patients with severe AH prospectively treated with corticosteroids were: (1) to generate a specific prognostic model, the socalled Lille model, enabling clinicians to identify subjects early on who are unlikely to survive; and (2) to propose new management based on this specific model.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…16 The Glasgow alcoholic hepatitis score is another recently developed model that takes age, white blood cell count, blood urea nitrogen concentration, prothrombin time ratio, and serum bilirubin concentration into consideration. 17 Although this model is easier to use at the bedside, its superiority for predicting mortality as compared with other models requires further evaluation. The Lille model is a newer model that predicts survival in patients with AH treated with corticosteroids by using a combination of 6 variables (age, renal function, albumin, prothrombin time, bilirubin, 7-day change in bilirubin).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Pentoxifylline a tumor necrosis factor a (TNF a) antagonist has shown promising results in the treatment of patients with severe alcoholic hepatitis. In the landmark study Akriviadis et al showed in a randomized controlled trial of 101 patients with severe alcoholic hepatitis that pentoxifylline significantly reduced the mortality from 46.1% in the placebo group to 24.5% in the pentoxifylline group (P < 0.037).…”
Section: Commentsmentioning
confidence: 99%